2015
DOI: 10.1021/jacs.5b09824
|View full text |Cite
|
Sign up to set email alerts
|

Complete Switch of Selectivity in the C–H Alkenylation and Hydroarylation Catalyzed by Iridium: The Role of Directing Groups

Abstract: A complete switch in the Cp*Ir(III)-catalyzed paths between C-H olefination and hydroarylation was found to be crucially dependent on the type of directing groups. This dichotomy in product distribution was correlated to the efficiency in attaining syn-coplanarity of olefin-inserted 7-membered iridacycles. Theoretical studies support our hypothesis that the degree of flexibility of this key intermediate modulates the β-H elimination, which ultimately affords the observed chemoselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(54 citation statements)
references
References 82 publications
5
47
0
2
Order By: Relevance
“…Meanwhile, α,β‐unsaturated esters appear to favor a β‐hydride elimination, furnishing the olefinic products . There are however notable exceptions to this which demonstrate scope for control, for example, Chang described that the selectivity could be influenced by the nature of the directing group, whilst Loh demonstrated that through the use of strong electron withdrawing substituents, olefinic products could be obtained from α,β‐unsaturated ketones and Ramana highlighted that absence/presence of a base could be the controlling factor …”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, α,β‐unsaturated esters appear to favor a β‐hydride elimination, furnishing the olefinic products . There are however notable exceptions to this which demonstrate scope for control, for example, Chang described that the selectivity could be influenced by the nature of the directing group, whilst Loh demonstrated that through the use of strong electron withdrawing substituents, olefinic products could be obtained from α,β‐unsaturated ketones and Ramana highlighted that absence/presence of a base could be the controlling factor …”
Section: Introductionmentioning
confidence: 99%
“…[167] Darüber hinaus wurde gezeigt, dass ein kationischer hochvalenter Cp*Co III -Komplex effizient die dirigierte Alkylierung mit konjugierten Alkenen katalysiert. So lieferte die iridiumkatalysierte ortho-Alkylierung derartiger Substrate mit konjugierten Alkenen lineare Produkte, [169] während sich Reaktionen mit Vinylethern als verzweigt-selektiv erwiesen. So lieferte die iridiumkatalysierte ortho-Alkylierung derartiger Substrate mit konjugierten Alkenen lineare Produkte, [169] während sich Reaktionen mit Vinylethern als verzweigt-selektiv erwiesen.…”
Section: Angewandte Chemieunclassified
“…[168] Iridiumkatalyse ist ebenfalls nützlich fürd ie N-Heteroaren-dirigierte Alkylierung von Arenen, besonders fürd ie Entwicklung enantioselektiver Va rianten, allerdings mit speziellen Substraten. So lieferte die iridiumkatalysierte ortho-Alkylierung derartiger Substrate mit konjugierten Alkenen lineare Produkte, [169] während sich Reaktionen mit Vinylethern als verzweigt-selektiv erwiesen. [170] Dies ebnete folgerichtig den Wegz ur Entwicklung enantioselektiver Versionen, [171] kulminierend in einem aktuellen Bericht von Nishimura et al zur enantioselektiven Hydroxyalkylierung mit Allylethern -d ie vor der Alkylierung in situ zu Vinylethern isomerisierten -m it einem kationischen Iridium/BINAP-Katalysator (Schema 37, Einschub * 6 ).…”
Section: Angewandte Chemieunclassified
“…In contrast, the square planar geometry of the palladium fits very well with the structure required for the reductive elimination process. 13 This dichotomy associated with the metal geometry might also explain other divergent outcomes of reactions promoted by Rh(III) or Pd(II). 5 …”
mentioning
confidence: 99%